The Effect of Life Design Online Career Counseling to Improve the Career Adaptability and Optimism - Istiqomah, Mufidah; Sugiyo, Sugiyo; Sunawan, Sunawan (Universitas Negeri Semarang, 2023)
Career adaptability and optimism are significant bases for adolescents in career decisions making and learning behavior. Thus, the present research attempted to examine the effects of life design online career counseling on students’ career adaptability and optimism. It was carried out in form of an experimental research with the design of randomized pretest-posttest control group and involved 15 students as the samples chosen using a purposive sampling technique. Their data were collected using the instruments of career adaptability scale and career future inventory. In testing the hypothesis, Wilcoxon signed rank and Kruskal Wallis tests with the probability of 95% were performed through SPSS version 26 software. The findings indicated that the life design online career counseling was able to improve students’ career adaptability and optimism. It somehow has ensured the potential of efficacy of using websites in applying life design career counseling.